Distributional analysis of Ghana's tax system - Abdul Malik Iddrisu; David Phillips; Benjamin Kamal Chackson; Tom Blanchard (Institute for Fiscal Studies (IFS), 2023)
In recent years, policymakers across the globe have become increasingly interested in not only the revenue consequences of tax policies but also their distributional impacts: that is, their impacts on different segments of the population. Such evidence can promote a more equitable and welfare-enhancing tax and benefit system, helping distinguish policies which may help meet a government's objectives for inclusive development from those which may have unintended or undesirable effects on low- and middle-income households. In this context, the Centre for Tax Analysis in Developing Countries (TaxDev), in collaboration with the Tax Policy Unit (TPU) at the Ghanaian Ministry of Finance, has built a microsimulation model of Ghana's tax system. This model (called GHATAX) uses micro-level data on household incomes and characteristics from the Ghana Living Standard Survey (GLSS) and macro-data based on the structure of Ghana's economy from Ghana's Social Accounting Matrix (SAM) in order to estimate the distributional effects of the main elements of Ghana's direct and indirect tax systems, such as personal income tax (PIT) and value added tax (VAT). In this report, we use GHATAX to analyse the distributional effects of Ghana's tax system as of December 2022, as well as the effects of reforms announced in the 2023 Budget.
Keywords: 330; International development; Poverty; inequality and social mobility; Taxes and benefits; Distributional effects; Gender; Income taxes; Low and middle income countries; Inequality; Poverty; Public finance; Tax; Taxes on wealth and spending; VAT